Israel, Islam and armageddon - Hunt, Dave.; Total Content (Firm); Berean Call (Organization) ([New Canaan, Conn.] : Distributed by Total Content, 2006)
With more than 3,000 years of history, Jerusalem is mentioned 800 times in the Bible, and is prophesied to play a key role in world destiny. This program shows how the current peace process is fraught with peril, why it is impossible for Jerusalem to know true peace in our age, how the Antichrist will lead the world's armies to destroy Israel, the truth about the Vatican's intentions, and the Palestinian myth.
DVD.
"The final battle for Jerusalem. Prophecy revealed!"--Case insert.
Host, Dave Hunt.
Special features: Dave Hunt presentation; Q & A.
Summary adapted from case insert.
Keywords: Bible -- Prophecies -- Jerusalem; Jerusalem in the Bible; Arab-Israeli conflict; Armageddon; Documentary films; Nonfiction films